Lotus‐Root‐Like Carbon Fibers Embedded with Ni–Co Nanoparticles for Dendrite‐Free Lithium Metal Anodes. Issue 24 (7th May 2021) - Chen, Chen; Guan, Jun; Li, Nian Wu; Lu, Yue; Luan, Deyan; Zhang, Cai Hong; Cheng, Guang; Yu, Le; Lou, Xiong Wen (David)
Abstract: The growth of lithium (Li) dendrites and the huge volume change are the critical issues for the practical applications of Li‐metal anodes. In this work, a spatial control strategy is proposed to address the above challenges using lotus‐root‐like Ni–Co hollow prisms@carbon fibers (NCH@CFs) as the host. The homogeneously distributed bimetallic Ni–Co particles on the N‐doped carbon fibers serve as nucleation sites to effectively reduce the overpotential for Li nucleation. Furthermore, the 3D conductive network can alter the electric field. More importantly, the hierarchical lotus‐root‐like hollow fibers provide sufficient void space to withstand the volume expansion during Li deposition. These structural features guide the uniform Li nucleation and non‐dendritic growth. As a result, the NCH@CFs host enables a very stable Li metal anode with a low voltage hysteresis during repeated Li plating/stripping for 1200 h at a current density of 1 mA cm −2 . Abstract : Lotus‐root‐like carbon fibers embedded with Ni–Co nanoparticles (NCH@CFs) are designed as a lithium (Li) host via facile electrospinning and the subsequent thermal annealing. Benefitting from the 3D conductive framework and the internal hollow structure with highly dispersed lithiophilic sites, the NCH@CF host can spatially regulate the electric field to effectively suppress the Li‐dendrite growth and withstand severe volume expansion for long‐term cycling performance in both symmetric and full cells.